(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article presents an analysis of materials such as articles, scientific developments covered in the last 15 years on the results of some scientific studies related to the nutrition and health indicators of military personnel on various sites in the Internet system. The article presents the results of the study of the relationship between the level of health, changes in weight indicators, the decrease in working capacity and the amount of testosterone hormone in their bodies, and the existence of a relationship between the diet of military personnel and their health. Also, information about the immune function of military personnel and the relationship of infection with infectious diseases with their nutrition is reflected.